The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1097/prs.0b013e318196b9a3
|View full text |Cite
|
Sign up to set email alerts
|

Techniques of Monitoring Buried Fasciocutaneous Free Flaps

Abstract: Temporarily externalizing a segment of tissue is an easy and reliable method for monitoring a buried fasciocutaneous free flap. It is important, however, to avoid obstruction at the perforator level beyond the common source vessels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 25 publications
0
69
0
2
Order By: Relevance
“…177 Often, implantable Doppler systems represent the only available form of monitoring in buried flaps, although some authors have reported success with temporarily externalizing implanted flaps (Level V Evidence). 178 Kind et al demonstrated in a series of 147 flaps the implantable Doppler was able to salvage 100 percent of flap take-backs (Level IV Evidence). 179 In a study of 103 patients undergoing 121 microvascular anastomoses, the negative predictive value of the implantable Doppler study system was 100 percent (Level IV Evidence).…”
Section: Postoperative Monitoringmentioning
confidence: 97%
“…177 Often, implantable Doppler systems represent the only available form of monitoring in buried flaps, although some authors have reported success with temporarily externalizing implanted flaps (Level V Evidence). 178 Kind et al demonstrated in a series of 147 flaps the implantable Doppler was able to salvage 100 percent of flap take-backs (Level IV Evidence). 179 In a study of 103 patients undergoing 121 microvascular anastomoses, the negative predictive value of the implantable Doppler study system was 100 percent (Level IV Evidence).…”
Section: Postoperative Monitoringmentioning
confidence: 97%
“…Ferguson and Yu [10 ] do recommend that care should be taken not to strangulate the perforator to the externalized component during the placement of this externalized segment.…”
Section: Discussionmentioning
confidence: 97%
“…Ferguson and Yu [10 ] describe their technique for monitoring buried flaps. They present a case series of 94 free flaps, most of which were anterolateral thigh flaps, used in laryngotracheal and pharyngeal reconstruction.…”
Section: Externalization Of a Component Of The Free Flapmentioning
confidence: 99%
“…Die Autoren glauben jedoch, dass der Nutzen der klinisch einfach umsetzbaren und nicht teuren Hautinsel auch eine sekundäre Entfernungin Lokalanästhesie -rechtfertigt. Sie ermöglicht eine kontinuierliche und für das medizinische Fachpersonal leicht durchführbare Möglichkeit zur Beurteilung der Durchblutung des Transplantates [17]. Zu bedenken bleibt, dass eine Torsion oder Druck auf die Gefäßpedikel der Hautinsel, z.…”
Section: Introductionunclassified